Strategi Marketing Mix Ikan Cakalang Asar (Studi Terhadap Pedagang Ikan Asar di Kota Ambon) - Fitria Karnudu; Fitri Indralia Mossy (IAIN Ambon, 2017)
The marketing strategy greatly affect the progress of the business, both in small and large scale. One type of business that developed the merchant in the city of Ambon is the smoked fish business, better known locally by the term asar fish. In carrying out its business, fish traders asar in Mardika Market and Small Hative Ambon has used a marketing strategy, but it is still traditional in nature. Its products are not designed to permanently, either packaging or labeling. The price set by the merchant using a strategy of price mark-up, differential, and the cost plus pricing strategy. Traders also use the direct distribution strategy, namely asar fish are sold directly to consumers. Whereas in promoting asar fish produced most traders use promotional strategies through personal selling, sales promotion and direct marketing. However, the strategy undertaken by fish asar in Ambon City traders have not been able to support the business expanded significantly. Keyword: marketing mix, merchants, smoked fish